The use of reciprocating file system in root canal curvature preparation: Penggunaan reciprocating file system dalam preparasi kurvatura saluran akar - Rachmuddin, Afniati; Rumagit, Hendra Wahyudi (Makassar Dental Journal PDGI Makassar, 2025)
One of the important steps in endodontic treatment is root canal preparation using files. Instrumentation difficulties in significantly curved root canals increase with increasing curvature angles, so adequate equipment is needed to handle them. In root canal preparation using a machine, there are two types of file movements commonly used: continuous rotation (CR) motion and reci-procating motion. The CR has several drawbacks, including the risk of file fracture due to interlocking and the need for multiple file sizes, which prolongs treatment time. The Reciprocating File System (RFS) is of interest because it can use a single file and has good resistance to torsional failure and cyclic fatigue. This study examines the effectiveness and efficiency of RFS in root canal curvature preparation. It is concluded that RFS is nearly as effective as CR but more efficient because it can use a single file and, specifically, has resistance to interlocking in the root canal as it does not easily lock.